Correlation Analysis of Anxiety and Mathematical Self-Efficacy on Problem Solving Ability Class XI IPA SMAN 2 Rumbiojaya - Wina Jamalia; Adityawarman Hidayat; Kasman Ediputra (Edumaspul: Jurnal Pendidikan, 2023)
Solving math problems is important in learning mathematics. In fact, there are still many students who do not like mathematics. This is due, among other things, to the difficulty of understanding mathematics. These difficulties have an impact on student learning outcomes. Student learning outcomes can be optimal if students believe in their abilities. Confidence that students lack can cause anxiety. Anxiety is considered as one of the inhibiting factors in solving math problems. This is what prompted the researcher to conduct a study entitled "Analysis of Mathematical Anxiety and Mathematical Self-Efficacy on the Mathematical Problem Solving Ability of Class XI IPA Students of SMAN 2 Rumbio Jaya. This study aims to determine whether or not the influence of mathematical anxiety and mathematical self-efficacy of students together on problem-solving abilities. The benefit of research for researchers is as an exercise in carrying out scientific research and for teachers is knowing things that affect problem-solving abilities. This research is a type of quantitative descriptive research using frequency distribution and correlation analysis techniques. The population in the study was students of class XI IPA SMAN 2 Rumbio Jaya. The sample selection used a purposive sampling technique. Data collection instruments use questionnaires and tests. Questionnaires were used to obtain data about students' mathematical anxiety and mathematical self-efficacy while tests were used to obtain data about problem solving abilities. The results of the study show that mathematical anxiety and mathematical efficacy are related to problem solving abilities with a coefficient of determination of 0.078% and 21.25%